HUBUNGAN INTENSITAS MELAKSANAKAN SHALAT TAHAJUD DENGAN STRES MAHASISWA DALAM MENGHADAPI UJIAN KOMPETENSI KEPESANTRENAN DI UNIVERSITAS IBRAHIMY - Saifullah; Siti Hidayatus Sholehah (Fakultas Dakwah Universitas Ibrahimy, 2024)
Stress is a condition caused by a person perceiving himself differently between physical and psychological demands. The aim of this research is to empirically test the relationship between the intensity of performing the tahajjud prayer and student stress in facing the Islamic boarding school competency exam at Ibrahimy University, Situbondo. The research method used is a quantitative research method with a correlation research type. In the research results, the guidelines for the degree of relationship show results with a Pearson value of 0.414. and a significant value of 0.025. So it can be concluded that the more intensively a person performs the tahajjud prayer, the lower the level of stress experienced. Likewise, the lower a person performs the Tahajjud prayer, the higher the level of stress he experiences.